2002
DOI: 10.1016/s0005-2736(01)00427-8
|View full text |Cite
|
Sign up to set email alerts
|

Human erythroid cells are affected by aluminium. Alteration of membrane band 3 protein

Abstract: There is evidence that anaemia is associated with aluminium (Al). We have already reported on the sensitivity to Al, showed by erythroid cell populations of animals chronically exposed to the metal. In order to investigate whether Al could also affect human cells, experiments were carried out both on immature and mature human erythroid cells. Erythroid progenitors (CFU-E, colony-forming units-erythroid) concentrated from human peripheral blood were cultured in an Al-rich medium under erythropoietin stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 16 publications
2
24
1
Order By: Relevance
“…3, RBCs from aluminium-intoxicated rats showed a diminution in osmotic fragility (lower 50·), which would imply a stabilisation against hypotonic haemolysis. From our experience, both stated causes could be possible: Al (III) can produce a membrane expansion as consequence of its effect upon the organisation of the membrane components; or can also lead to an increased ion permeability (Vittori et al [35] proved that Al (III) alters Band 3, the anion channel; furthermore, Isom [36] points out that Al (III) affects the Na + channel). Another possible cause for higher lysis resistance could be a lesser haemoglobin content produced by Al (III), allowing a larger water intake before lysis.…”
Section: Discussionmentioning
confidence: 91%
“…3, RBCs from aluminium-intoxicated rats showed a diminution in osmotic fragility (lower 50·), which would imply a stabilisation against hypotonic haemolysis. From our experience, both stated causes could be possible: Al (III) can produce a membrane expansion as consequence of its effect upon the organisation of the membrane components; or can also lead to an increased ion permeability (Vittori et al [35] proved that Al (III) alters Band 3, the anion channel; furthermore, Isom [36] points out that Al (III) affects the Na + channel). Another possible cause for higher lysis resistance could be a lesser haemoglobin content produced by Al (III), allowing a larger water intake before lysis.…”
Section: Discussionmentioning
confidence: 91%
“…Inhibition of erythroid progenitor cells by Al has been demonstrated by both in vitro and in vivo assays. Severe morphological changes of erythrocytes were induced by Al, and traces of the metal were detected inside cells with abnormal shape [274] or attached to the erythrocyte membrane [275]. Al toxicity continues to be a problem for chronic hemodialysis patients.…”
Section: Induction Of Interfacial Water Stressmentioning
confidence: 99%
“…Several studies reported that Al damages the molecular structure, deformability, and fluidity of erythrocyte membrane by inducing lipid peroxidation and oxidative stress [27,[29][30][31]. Moreover, Suwalsky et al found that Al disorders the ion balance between intracellular and extracellular, which affects the transport function of membrane [32].…”
Section: Introductionmentioning
confidence: 99%